Uncommon occurrence of lip squamous cell carcinoma in a pediatric patient - Tomo, Saygo [UNESP]; Da Silva Santos, Ingrid [UNESP]; Stefanini, Aline Reis; De Oliveira Cucolicchio, Guilherme; Miyahara, Glauco Issamu [UNESP]; Simonato, Luciana Estevam (My University, 2017)
Although head and neck squamous cell carcinoma represents one of the most common cancers among adults, it is rare in pediatric patients. The purpose of this report is to discuss the case of a 15-year-old male patient referred by his dentist due to a threemonth old ulcer in his lower lip. The patient denied tobacco smoking and drinking alcohol, and confirmed that he performed manual labor in a brick yard, being exposed daily to the sun without protection. Clinical examination revealed an exophytic rounded ulcer in the right lower lip, measuring 1.5 cm, with a flaky bed. An incisional biopsy was performed, and histopathologic analysis confirmed the diagnosis of squamous cell carcinoma. The treatment of choice was surgical excision. Malignancy should be included in the differential diagnosis of chronic oral ulcers in children and adolescents. Moreover, chronic sun exposure might be associated with occurrence of lip squamous cell carcinoma.
Keywords: Lip neoplasms; Oral neoplasms; Pediatric dentistry